Evaluation of Bone Consolidation in External Fixation with an Electromechanical System - Maria F. Paulino; Luis M. Roseiro; Inês Balacó; Maria A. Neto; Ana M. Amaro (Applied Sciences, 2022)
The monitoring of fracture or osteotomy healing is vital for orthopedists to help advise, if necessary, secondary treatments for improving healing outcomes and minimizing patient suffering. It has been decades since osteotomy stiffness has been identified as one main parameter to quantify and qualify the outcome of a regenerated callus. Still, radiographic imaging remains the current standard diagnostic technique of orthopedists. Hence, with recent technological advancements, engineers need to use the new branches of knowledge and improve or innovate diagnostic technologies. An electromechanical system was developed to help diagnose changes in osteotomy stiffness treated with the external fixator LRS Orthofix®. The concept was evaluated experimentally and numerically during fracture healing simulation using two different models: a simplified model of a human tibia, consisting of a nylon bar with a diameter of 30 mm, and a synthetic tibia with the anatomical model from fourth-generation Sawbones®. Moreover, Sawbones® blocks with different densities simulated the mechanical characteristics of the regenerated bone in many stages of bone callus growth. The experimental measurements using the developed diagnostic were compared to the numerically simulated results. For this external fixator, it was possible to show that the displacement in osteotomy was always lower than the displacement prescribed in the elongator. Nevertheless, a relationship was established between the energy consumption by the electromechanical system used to perform callus stimulus and the degree of osteotomy consolidation. Hence, this technology may lead to methodologies of mechanical stimulation for regenerating bone, which will play a relevant role for bedridden individuals with mobility limitations.